An extensive review: How starch and gluten impact dough machinability and resultant bread qualities. Issue 13 (19th May 2023) - Hu, Xiaohui; Cheng, Li; Hong, Yan; Li, Zhaofeng; Li, Caiming; Gu, Zhengbiao
Abstract: Wheat flour can form dough with a three-dimensional viscoelastic structure that is responsible for gas holding during fermentation and oven-rise, creating a typical fixed, open-cell foam structure of bread after baking. As the major components of dough, the continuous reticular skeleton formed by gluten proteins and the concentrated starch granules entrapped in gluten matrix predominantly determine dough rheological behaviors and bread qualities. This review surveys the latest literatures and draws out a conclusion from a plethora of information related to the filling effects of starch granules on gluten matrix and the cross-linking mechanisms between gluten proteins and starch granules, which is of great significance to provide sufficient scientific knowledge for development of bread with satisfactory attributes and quality control of end products.